The Effect of Conservation Knowledge on Attitudes and Stated Behaviors toward Arthropods of Urban and Suburban Elementary School Students - Cornelisse, Tara; Sagasta, Jacquelyn (Anthrozoös, 2018)
Arthropods provide ecosystem services upon which humans depend, yet are declining across the globe. Arthropods are neglected from conservation efforts due to many factors that include a lack of understanding of their roles and conservation need. Knowledge gain of arthropod roles could therefore increase support for their conservation, albeit indirectly through attitude changes. Evidence suggests knowledge and attitudes are more highly correlated in children and that environmental attitudes are shaped before age 12 years. Differences in the connection between knowledge, attitudes, and behaviors toward arthropods may also be different in children from different cultures or from urban versus rural locations due to varying experiences with arthropods. We sought to understand if different types of knowledge increased positive attitudes and stated conservation-based behaviors toward insects in children in both urban and suburban schools. We conducted either a basic biology lesson or a conservation lesson on ecosystem services in both urban and suburban 4th and 5th grade classes, and used pre- and post-questionnaires to detect changes in knowledge, attitudes, and stated behavior toward arthropods. We found that urban students had significantly lower knowledge of, less positive attitudes toward, and fewer stated conservation behaviors toward arthropods but also exhibited the greatest positive changes when presented the conservation-based lesson. In addition, we found that being able to identify the type of arthropod correctly was related to more positive attitudes and stated behaviors. Finally, we found that while attitudes did not change toward some species, stated conservation behaviors did increase with knowledge of the arthropod’s role in the ecosystem. Education in urban schools, with a focus on both distinguishing arthropods as well as ecosystem services, provides the most change per effort for conservation. Arthropod lessons could be done by local professors and undergraduate students in urban classrooms or local green spaces.